Financial Management Information System Website for Contributions in Taman Kradenan Asri Cluster Area - Namudani, Ninggar; Nugroho, Agus Cahyo; Widiantoro, Albertus Dwiyoga (Soegijapranata Catholic University, 2024)
A social contribution payment system in a housing estate is usually applied for specific purposes. At Taman Kradenan Asri Cluster Area several fees are imposed. The system used today is still conventionally applied, where the person assigned to collect the contribution bill records when payment is made in a book. Because there are several fees, several books are needed and adjusted to the type of contribution. This system requires more workforce and costs and allows human error to occur. Besides, residents cannot access it to check their bills. Therefore, research was carried out with the title